Different Views of English Tense System (Eurasian Research Bulletin, 2023)
This article is depending on the tense category is universally recognized. Nobody has ever suggested to characterized the distinction, for example, between wrote, writes, and will write as other than a tense distinction. So the question is how to define the category as such, and what distinctions within the category of tense can be found, in other words how many tenses there are in English